Promoting Competition in Public Procurement System - Simonyan, Aram (Bulletin of Yerevan University G: Economics, 2014)
The competition is the driver of the market economy hence the obstacles such as corruption and its manifestations that detiorate fair competition need to be eliminated. In case of lack of real competition the corruption as a cancer penetrates into the economy, completely weakens it and ruins the economy in the end. Due to the analysis, in this article we studied the main developments in the procurement system in line with the ongoing problems and possible solutions. Summarizing, we can admit that despite the huge attention to the procurement system, essential contradictions and legal loopholes as well as procedurial problems still exist that enable manipulation in the process of procurement and consequently increase corruption risks. Therefore the main precondition for success is the modernization of the whole system and the promotion of genuine competition by applying systematic approach in order to avoid the vicious circle.
Keywords: competition, procurement system, corruption, e-procurement, shadow economy